Informed Consent in Blood Transfusion: How "Informed" Is the Consent if Someone Is on a Controlled Substance?. (21st September 2018) - Maris, Alexander; Booth, Garrett
Abstract: The bioethical principle of autonomy warrants informed consent for blood transfusion, including discussion of indications, risks, benefits, and alternatives. AABB Standards mandate this process—and its documentation—with periodic review by transfusion service medical directors. The literature shows that patients, at baseline, are intrinsically comfortable receiving transfusion despite poor understanding of the above elements. We question how patients fare when they receive controlled substances (opiates and benzodiazepines) prior to the consent process. But first we ask, in nonemergent inpatients undergoing first-time blood transfusion and who recently received narcotics, what was the timing between the last narcotic dose and the consent process for transfusion? We hypothesize that clinicians do not always account for these medications when timing informed consent. Our laboratory information system was queried for first-time patient recipients of blood transfusion between 2010 and 2016. The first 290 patient records were reviewed. Nonemergent adult inpatients were included; ambulatory, emergent/trauma, and altered patients were excluded. The consent document timestamp and peri-transfusion history were recorded. The timestamp from last narcotic dose before consent was recorded, and time from consent was calculated. In total, 146/290 (50%) of patients were excluded. Among included patients, 92/144 (64%) had no consent document or an expired consent per institutional policy, and 20/144 (14%) had incomplete consent forms, including missing timestamps. Only 8/144 (6%) had unambiguous documentation of having received narcotics (IV or oral) within the 24 hours preceding consent. Timing before consent ranged from 12 minutes to 18.5 hours with a mean of 6.2 hours. It is difficult to assess frequency and timing of narcotics administration before transfusion consent when AABB-mandated documentation is absent or incomplete. Transfusion service medical directors and clinicians must develop robust systems to ensure adequate documentation of transfusion consent. Only then can we examine the possibility of narcotics negatively impacting the informed consent process.